2023
DOI: 10.3390/su15086506
|View full text |Cite
|
Sign up to set email alerts
|

E-Leadership Is Un(usual): Multi-Criteria Analysis of Critical Success Factors for the Transition from Leadership to E-Leadership

Abstract: Leadership helps to build strong organizations with resilient cultures. It is established that leadership needs a transition powered by digital technologies to tackle the shift from workplace culture to remote work, which is being practiced even after the pandemic to reduce operational costs and improve flexibility. The transition from leadership to e-leadership requires a profound understanding of the critical success factors (CSFs). The primary objective of this study is to identify the critical success fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Hence, the findings of our study support H4, H5, and H6 and are in line with the previous research that has found a significant impact of individual EI on work-related outcomes [68,86]. A recent study by Ahuja et al [87] also supports our study argument that VL can make individuals feel isolated and disconnected, if not appropriately managed, which can consequently enhance stress and impact the well-being of the workforce in the organization. Nurses with high EI can regulate their emotions based on the needs of the situation, which helps keep them involved in work and keeps them physically and mentally strong.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the findings of our study support H4, H5, and H6 and are in line with the previous research that has found a significant impact of individual EI on work-related outcomes [68,86]. A recent study by Ahuja et al [87] also supports our study argument that VL can make individuals feel isolated and disconnected, if not appropriately managed, which can consequently enhance stress and impact the well-being of the workforce in the organization. Nurses with high EI can regulate their emotions based on the needs of the situation, which helps keep them involved in work and keeps them physically and mentally strong.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, an integrative approach that includes flawed leaders, susceptible followers, and conducive environments that can form a toxic triangle is required when reviewing destructive leadership (Thoroughgood et al, 2018). Therefore, what all of this emphasizes is that leadership is a dynamic and co-creational process between the leader, employee/follower, and the workplace that can affect individual, group, and organizational outcomes (Ahuja, Puppala, Sergio & Hoffman, 2023;Dabke, 2016;Omer et al, 2022).…”
Section: Workplace Toxicitymentioning
confidence: 99%
“…Hence, developing a skilled and resultsoriented workforce requires ethical and responsive leadership practices (Ahuja et al, 2023) to create an innovative workplace environment (Faccia et al, 2023) conducive to supporting employees' PE towards improved productivity, collaboration, constructive interaction, and achievement of set objectives (Paola, Coello-Montecel & Tello, 2023).…”
Section: Psychological Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership style shows a leader's characteristics, skills, and behavior as they perform their duties [6]. Therefore, facing the challenges of today's digital age, it is appropriate to adopt digital leadership to achieve organizational goals [7]. Digital leaders act as individuals who add value to the organization by integrating leadership skills with digital technology.…”
Section: Introductionmentioning
confidence: 99%